Case Series: Iatrogenic Penile Amputation Due to Circumcision - Satyagraha, Paksi; Mumpuni I.A, Fusarina; Seputra, Kurnia Penta (International Journal of Psychosocial Rehabilitation, 2020)
Penile amputation is the most common complications of guillotine circumcision. There are three cases of iatrogenic penile amputation due to circumcision in Saiful Anwar General Hospital Malang in last 5 years. This series contains three cases of iatrogenic penile amputation due to circumcision in Saiful Anwar General Hospital Malang within 2013-2018 and all of them taken from hospital medical record. One of them already done replantation of penile but unsuccessful due to the preserved of the cutout and the ischemic time of the wound. All of them get the injury due to Guillotine technique that perform by unexperienced person. In cases of microphallus, buried penis, hypospadias, epispadias, phimosis and penoscrotal webbing the circumcision should be performed by a surgeon. Guillotine techniques are not safe for patients under 10 years old, because increase the risk of penile injury.